2019
DOI: 10.3390/ijms20112723
|View full text |Cite
|
Sign up to set email alerts
|

Betula etnensis Raf. (Betulaceae) Extract Induced HO-1 Expression and Ferroptosis Cell Death in Human Colon Cancer Cells

Abstract: Betula etnensis Raf. (Birch Etna) belonging to the Betulaceae family grows on the eastern slope of Etna. Many bioactive compounds present in Betula species are considered promising anticancer agents. In this study, we evaluated the effects of B. etnensis Raf. bark methanolic extract on a human colon cancer cell line (CaCo2). In order to elucidate the mechanisms of action of the extract, cellular redox status, cell cycle, and heme oxygenase-1 (HO-1) expression in ferroptosis induction were evaluated. Cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
(51 reference statements)
0
74
0
1
Order By: Relevance
“…LDH is a soluble cytoplasmic enzyme that is present in almost all cells and is released into extracellular space due to the loss of membrane integrity in dying cells. Thus, the determination of LDH release can be utilized as a useful method for detection of necrosis, and therefore as a measure of cytotoxicity [45,46]. The capacity of a plant extract to induce necrotic cell death could potentially be a valuable adjunctive therapy in cancer treatment [47].…”
Section: Discussionmentioning
confidence: 99%
“…LDH is a soluble cytoplasmic enzyme that is present in almost all cells and is released into extracellular space due to the loss of membrane integrity in dying cells. Thus, the determination of LDH release can be utilized as a useful method for detection of necrosis, and therefore as a measure of cytotoxicity [45,46]. The capacity of a plant extract to induce necrotic cell death could potentially be a valuable adjunctive therapy in cancer treatment [47].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle analysis was performed on untreated and 24 h treated cells with Rapha Myr ® extract (0.5–1.25–2.5% v/v ), according to Malfa et al, 2019 [ 70 ]. In order to assess cell cycle state, 1 × 10 6 cells were stained with propidium iodide (PI, 50 ng/mL) and analyzed by the FlowSight ® (Amnis ® , part of EMD Millipore) imaging flow cytometer.…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely demonstrated that environmental factors, including diet, lifestyle habits, and natural compounds, are responsible for both genetic and epigenetic alterations predisposing the development of several diseases, and have beneficial effects in preventing the development of chronic-degenerative disorders (133)(134)(135)(136)(137)(138)(139)(140). In particular, dietary intake and food consumption modulate several cellular and molecular processes acting in a multifactorial manner (141)(142)(143). Indeed, the consumption of specific food and nutrients may modulate inflammatory and cell cycle regulatory pathways to maintain the optimal cell homeostasis, preventing the development of diseases (144,145).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%